Effect of Residual Oxygen Concentration on the Lattice Parameters of Aluminum Nitride Powder Prepared via Carbothermal Reduction Nitridation Reaction - Kim, Jaegyeom; Ahn, Heewon; Kim, Seung Joo; Kim, Jong Young; Pee, Jae Hwan (Materials, 2022)
Residual oxygen in wurtzite-type aluminum nitride (AlN) crystal, which significantly affects phonon transport and crystal growth, is crucial to thermal conductivity and the crystal quality of AlN ceramics. In this study, the effect of residual oxygen on the lattice of AlN was examined for as-synthesized and sintered samples. By controlling reaction time in the carbothermal reduction nitridation (CRN) procedure, AlN powder was successfully synthesized, and the amount of residual oxygen was systematically controlled. The evolution of lattice parameters of AlN with respect to oxygen conc. was carefully investigated via X-ray diffraction analysis. With increasing amounts of residual oxygen in the as-synthesized AlN, lattice expansion in the ab plane was induced without a significant change in the c-axis lattice parameter. The lattice expansion in the ab plane owing to the residual oxygen was also confirmed with high-resolution transmission electron microscopy, in contrast to the invariant lattice parameter of the sintered AlN phase. Micro-strain values from XRD peak broadening confirm that stress, induced by residual oxygen, expands the AlN lattice. In this work, the lattice expansion of AlN with increasing residual oxygen was elucidated via X-ray diffraction and HR-TEM, which is useful to estimate and control the lattice oxygen in AlN ceramics.
Keywords: Aluminum nitride ceramics; Aluminum nitride crystals; Carbothermal reduction/nitridation; Lattice expansion; Nitridation reaction; Oxygen concentrations; Phonon transport; Residual oxygen; Synthesised; Wurtzite type; aluminum nitride; lattice parameter; nitrides; residual oxygen